2018
DOI: 10.1055/s-0037-1610086
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free Reduction of Nitro Aromatics to Amines with B2(OH)4/H2O

Abstract: A metal-free reduction of nitro aromatics mediated by di­boronic acid with water as both the hydrogen donor and solvent under mild conditions has been developed. A series of aromatic amines were obtained with good functional group tolerance and in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…1-Nitronaphthalene ( 1u ) and functionalized heterocyclic nitro compounds, such as those containing pyridine ( 1v and 1w ), quinoline ( 1x , 1y , and 1z ), benzimidazole ( 1aa ), benzoxazole ( 1ab ), or phthalimide ( 1ac ) moieties, have been proven to be tolerated by our reduction protocol to give the corresponding products ( 2u–2ac ) in high yields (at least 78% isolated yield). Notably, unlike previous B 2 (OH) 4 -based reduction methods that reduced both the nitro group and pyridine ring of quinoline, our method using similar compounds did not affect the pyridine ring of quinoline and only reduced the nitro group. , Interestingly, for a substrate with more than one nitro group on the aromatic ring ( 1ad ), only one of the nitro group was reduced to the corresponding amine even when the amount of B 2 (OH 4 ) was increased to 6 equiv ( 2ad ). Finally, for vinyl nitro ( 1ae ) or aliphatic nitro ( 1af ) substrates, reduction of the nitro group did not proceed.…”
Section: Results and Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…1-Nitronaphthalene ( 1u ) and functionalized heterocyclic nitro compounds, such as those containing pyridine ( 1v and 1w ), quinoline ( 1x , 1y , and 1z ), benzimidazole ( 1aa ), benzoxazole ( 1ab ), or phthalimide ( 1ac ) moieties, have been proven to be tolerated by our reduction protocol to give the corresponding products ( 2u–2ac ) in high yields (at least 78% isolated yield). Notably, unlike previous B 2 (OH) 4 -based reduction methods that reduced both the nitro group and pyridine ring of quinoline, our method using similar compounds did not affect the pyridine ring of quinoline and only reduced the nitro group. , Interestingly, for a substrate with more than one nitro group on the aromatic ring ( 1ad ), only one of the nitro group was reduced to the corresponding amine even when the amount of B 2 (OH 4 ) was increased to 6 equiv ( 2ad ). Finally, for vinyl nitro ( 1ae ) or aliphatic nitro ( 1af ) substrates, reduction of the nitro group did not proceed.…”
Section: Results and Discussionmentioning
confidence: 72%
“…Interestingly, under the optimized reaction conditions, reduction of the heteroaromatic ring has occurred alongside with the nitro group reduction. 18 Du et al reported a DNA-compatible nitro reduction using B 2 (OH) 4 and NaOH; however, halogenated nitroarenes underwent dehalogenation. 19 Recently, Hosoya et al reported the reduction of nitro groups using B 2 (OH) 4 or bis-(neopentylglycolato)diboron (B 2 nep 2 ), catalyzed by 4,4′bipyridine.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this reaction proceeded at significantly lower temperatures than previously reported, 14 we sought to further validate formation of the presumed on-DNA aniline product. Using similar conditions modified for decigram scale, nitroarene substrates 5 and 7 both provided the desired amine products in good or better isolated yield within 5 min (Scheme 3).…”
mentioning
confidence: 93%
“…This is consistent with a proposed mechanism for diboron-mediated nitro reduction, in which reduction is promoted by coordination of an alkoxide to boron. 14 We next set out to determine cosolvent effects, utilizing several common, water-miscible organic solvents. Use of acetonitrile, dimethylacetamide, dimethylformamide, and pure water provided lowered conversion to 2a , and although DMSO provided the aniline in excellent conversion, high amounts of DMSO may impair isolation of DNA (Table 1, entries 5–10).…”
mentioning
confidence: 99%